2020
DOI: 10.1021/acsami.0c04212
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Structural Evolution in Na-Excess Layered Cathodes for Rational Use of an Anionic Redox Reaction

Abstract: A new paradigm based on an anionic O 2− /O n− redox reaction has been highlighted in high-energy density cathode materials for sodium-ion batteries, achieving a high voltage (∼4.2 V vs Na/Na + ) with a large anionic capacity during the first charge process. The structural variations during (de)intercalation are closely correlated with stable cyclability. To determine the rational range of the anion-based redox reaction, the structural origins of Na 1−x Ru 0.5 O 1.5 (0 ≤ x ≤ 1.0) were deduced from its vacancy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…For transition-metal (Ru and Ir) 4d and 5d bands, a Hubbard type U correction was used, where the U values (2.0 eV for Ir and 4.0 eV for Ru) were taken from the previous literature. , For obtaining good numerical sampling, Brillouin zone sampling based on the Monkhorst–Pack method was used with 4 × 4 × 4 k -point meshes, and a cutoff energy of 530 eV was employed in all calculations. The Na-excess oxide models with 4 formula units, which are adequate to qualitatively show experimental results, were used, and total system energies were obtained from the fully relaxed structures with corresponding atomic coordinates and cell parameters for the thermodynamic energies, structural parameters, and charge variations. ,,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For transition-metal (Ru and Ir) 4d and 5d bands, a Hubbard type U correction was used, where the U values (2.0 eV for Ir and 4.0 eV for Ru) were taken from the previous literature. , For obtaining good numerical sampling, Brillouin zone sampling based on the Monkhorst–Pack method was used with 4 × 4 × 4 k -point meshes, and a cutoff energy of 530 eV was employed in all calculations. The Na-excess oxide models with 4 formula units, which are adequate to qualitatively show experimental results, were used, and total system energies were obtained from the fully relaxed structures with corresponding atomic coordinates and cell parameters for the thermodynamic energies, structural parameters, and charge variations. ,,, …”
Section: Methodsmentioning
confidence: 99%
“…Conventionally, cation redox reactions based on transition metals (TMs) in fully Li stoichiometric layered oxides (Li­[TM]­O 2 ) have been regarded a dominant factor for the charge compensation mechanism upon cycling. However, an intriguing redox chemistry via oxygen ions has emerged to achieve high-energy-density cathodes and has been intensively studied for the practical use of anion-utilization oxides for positive electrodes over the past five years. The possibility of utilizing the oxygen redox was considered for the first time for a Li-excess Mn layered oxide, Li 2 MnO 3 , with a honeycomb-ordered superstructure in the Mn layer, which exhibited an anomalous charge capacity at ∼4.5 V versus Li + /Li during delithiation. To determine the origin of the electrochemical activity in Li 2 MnO 3 , numerous experimental and theoretical studies have been carried out and revealed that the stabilized electronic structure of Mn 4+ (t 2g 3 e g 0 ) in the energetics of crystal field theory is not favorable for further oxidation to Mn 5+ at an octahedral complex, which leads to the redox participation of an oxygen-2p-electron-like Li–O–Li configuration located at high energy levels. However, the promising O redox features completely disappear in the subsequent discharge with a large voltage hysteresis after the first charge process in the Li-excess Mn oxide. , Inspired by the oxygen redox in LIBs, Na­[Li 1/3 Mn 2/3 ]­O 2 was designed rationally for the utilization of anion redox to overcome the limitation of energy density in SIBs . Various TM-based Na-layered oxides exhibiting oxygen redox activities have been introduced .…”
Section: Introductionmentioning
confidence: 99%
“…Ru-Based Compounds. The oxygen-redox chemistry was demonstrated in sodium-rich Ru-based cathodes with good structural stability [30][31][32][33][34][35][36][37][38][39][40][41][42]. The first research paper on such materials was published in 2013 by the group of Tamaru et al on Na 2 RuO 3 (R 3 m), in which Ru was stabilized as Ru 4+ [30].…”
Section: 2mentioning
confidence: 99%
“…Energy Material Advances and DFT calculation results showed that the existence of ordered Na vacancies played an essential role in increasing the O 2p electronic population near the Fermi level, which not only stabilized the phase transformations during cycling but also facilitated reversible oxygen-redox reactions (Figure 9(e)) [34]. Moreover, in a later work of Liu et al, the Mn 4+ -substitution strategy was adopted in Na 2 Ru 1-x Mn x O 3 (x = 0 -0:3) material [38].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation